Indices de manifestations culturelles de l'archaique : La région de Trois-Rivières - Marois, Roger J. M.; Ribes, Rene (Book collections on Project MUSE., 1975)
An analysis of remains recovered from two zones on a mound at Ste-Angele-de-Laval in 1973, as well as artifacts from neighbouring localities.